A eficiência técnica da pecuária de leite familiar e seus condicionantes no estado de Minas Gerais - Ladeira, Thiago Fernandes (2024)
This thesis aimed to investigate the technical efficiency conditions of dairy farming in the state of Minas Gerais, focusing on rural establishments that meet the criteria for family farming. Using data from public research and technical assistance programs in Minas Gerais, models based on Data Envelopment Analysis (DEA) and the stochastic frontier production function approach were employed to calculate technical efficiency scores for 149 dairy farms located in 124 municipalities across the state. Additionally, financial, productive, and demographic data, both from the production systems and the farmers themselves, were analyzed using a Tobit regression to identify potential factors influencing the efficiency scores. The analysis revealed that most efficiency levels fell below the maximum threshold, though they were still within high or medium-high ranges. The results indicated that isolated expenditures on feed, capital, and labor were statistically significant in reducing efficiency. Additionally, expanding the farmed area also had a negative impact on efficiency. Conversely, an increase in production scale, represented by the actual quantity produced, ceteris paribus, led to higher technical efficiency in dairy farming. Furthermore, the estimation of the translog production function, based on the collected data, showed that the most important inputs for determining sector output were expenditures on feed, capital, and other operating costs. climatic factors such as air temperature and precipitation also played a significant role in shaping the production function. Overall, it became clear that family dairy farming in Minas Gerais has reached a mature level of technical efficiency, with producers performing as expected in a competitive environment. However, it is essential to recognize that rural development requires a broader perspective than that applied to other economic sectors. In other words, if the role of family dairy farming in economic development is primarily to achieve technical efficiency and profitability, this objective has largely been met. Finally, the study suggests that if a persistent crisis exists in the dairy sector, it must also be investigated in other links of the dairy production chain.